Composite scintillators based on single crystal grains Y₂SiO₅:Ce (YSO) and Y₃Al₅O₁₂:Ce (YAG) - Galunov, N.Z.; Gerasymov, Ia.V.; Gorbacheva, T.E.; Grinyov, B.V.; Karavaeva, N.L.; Khabuseva, S.U.; Krech, A.V.; Levchuk, L.G.; Martynenko, E.V.; Popov, V.F.; Sidletskiy, O.Ts.; Sorokin, P.V.; et al. (Вопросы атомной науки и техники, 2017)
Radiation-resistant composite scintillators based on grains of inorganic single crystals of the yttrium orthosilicate Y₂SiO₅:Ce and yttrium aluminium garnet Y₃Al₅5O₁₂:Ce were studied. The irradiation of the samples by KIPT 10 MeV electron Linac causes the dose rate of 1,500 Mrad/h or 0.1 Mrad/h when it is 9.2 MeV beam electrons or bremsstrahlung photons, respectively. We run the measurements of light transmittance, luminescence spectra and scintillation light outputs of a scintillator before and after irradiation. The paper presents and analyzes the results obtained for scintillators exposed to doses about 25 Mrad (the dose rate is 0.1 Mrad/h) and 150 Mrad (the dose rate is 1,500 Mrad/h).